The researcher 'in the middle': Negotiating the insider/outsider dichotomy - Breen, Lauren (The College of Community Psychologists of the Australian Psychological Society, 2007)
Researchers, particularly those using qualitative methodologies, often position themselves as ‘insiders’ rather than ‘outsiders’ to their research domain. In this paper I discuss the role I occupied within my PhD research, including the personal experiences that led me to consider myself to be neither ‘inside’ nor ‘outside’ the research domain. I explore the ways in which my experience ‘in the middle’ influenced my choice of research topic, the scope of my study, access to informants, the collection and analysis of data, and the maintenance of research rigor. I argue that the insider/outsider dichotomy is simplistic, and the distinction is unlikely to adequately capture the role of all researchers. Instead, the role of the researcher is better conceptualised on a continuum, rather than as an either/ or dichotomy. My role as neither an insider-researcher nor outsider-researcher maximised the advantages of each while minimising the potential for disadvantages, and meant that I was able to benefit from both in my study of grief experiences responses following fatal vehicle crashes in Western Australia.